Long-term results of four horizontal rectus muscle recession in nystagmus treatment. (June 2014) - Atilla, Huban; Demir, Helin Deniz; Işıkçelik, Yusuf
Abstract Purpose: To report the long-term results of four horizontal rectus muscle recessions that were performed for infantile nystagmus syndrome treatment. Methods: In this case series, patients with infantile nystagmus syndrome who had four horizontal muscle recessions previously were recruited and ophthalmological examination and electronystagmography recordings were performed. Objectively, amplitude and frequency of nystagmus were measured from the recordings and the intensity was calculated. Visual acuity, stereopsis, and alignment were evaluated and compared with the preoperative and postoperative values. Results: The records of the 12 patients who had four horizontal rectus muscle recession surgery were evaluated and six patients (5 male, 1 female) who had regular follow-ups were included in this study. Mean follow-up was 14.17 ± 0.41 years (minimum 14 years, maximum 15 years) and mean age of patients at the last visit was 22 years (20-28 years). On subjective evaluation, two-thirds (4/6) of the patients were satisfied with the surgical results and had the impression that after surgery, nystagmus decreased in intensity and head posture improved. On objective evaluation, visual acuity was found to be the same, however, stereopsis improved (preoperatively and postoperatively median stereopsis was 600 sec arc vs 200 sec arc final). The decrease in nystagmus amplitude and frequency was still maintained. Conclusions: Nystagmus surgery on four horizontal rectus muscles has positive effects on binocular function and nystagmus parameters in the long-term follow-up. As we could not treat the primary pathology, the visual acuity was about the same but the decrease in nystagmus amplitude and frequency was still maintained with better stereopsis, and patient satisfaction.